EVALUASI PENGARUH DIMENSI CONSUMER CONFUSION PRONENESS TERHADAP PERILAKU KONSUMEN PADA PEMBELIAN PRODUK BUSANA MUSLIM - verdina parasmita (Neraca, 2015)
This reaserch aim to investigate the influence Similarity,Overload and Ambiguity confusion proneness to fifth consumer behavior,consisting of Word of Mouth (WOM),trust,consumer satisfation Desision postponemen and Share/delegate purchase.Data analysis using Structual Equation Modelling (SEM).The population in this research are Muslimah student at the Faculty of Economics and Business Jendral Soedirman University.Determination of the number of samples in this study were 225 respondest with a sampling methode used is using probability sampling and sample cellection technique is simple random sampling . Bsead on the result of hypothesis testing are known: (1a) there is no effect between similarity confusion proneness to WOM ;(1b) there is positif effect between similarity confusion proneness tp trust ;(1c) there is positif effect between similarity confusion proneness to consumer satisfaction ;(2a) there is negatif effect between overload confusion proneness to WOM ; (2b) There is negatif effect between overload confusion proneness to trust ; (2c) There is negatif effect between overload confusion proneness to consumer satisfaction ; (3a) There is positif effect between ambiguity confusion proneness to WOM ; (3b) There is positif effect between ambiguity confusion proneness to trust ; (3c) There is positif effect between ambiguity confusion proneness to consumer satisfaction ;(1d) (2d) (3d) There is no effect among similarity ,overload and ambiguity confusion proneness to decision postponement; (1e) (2e) (3e) There is no effect among similarity ,overload and ambiguity confusion proneness to share /delegate purchase.Based the discussion of the research results,it can be concluded that the general there is negative and pos impact between consumer confusion proneness dimension (Similarity,Overload Ambiguity) to the consumer behavior Muslim fasion ,although not all the dimensions of consumer confusion proneness directly impacts the fifth consumer behavior studied.